Dietary protein and carbohydrates affect immune function and performance in a specialist herbivore insect (Manduca sexta) - Wilson, J. K.; Ruiz, L.; Davidowitz, G.
Nutrition structures ecology and evolution across all scales of biological organization. It is well known that nutrition can have direct effects on performance and fitness, but indirect effects on physiological systems that mediate biotic interactions have been studied less frequently. Here, we focus on the interaction between nutrition, performance, and the immune system in a specialist herbivorous insect, Manduca sexta. We used a conceptual framework in nutritional ecology (the geometric framework)to examine how changes in diet quality affect aspects of the immune system used for defense against parasitoids. We raised caterpillars throughout their entire larval development on five different experimental diets that varied in protein and carbohydrate content and measured five aspects of the immune system: encapsulation, phenoloxidase activity, prophenoloxidase activity, total hemolymph protein, and hemocyte density. Overall, different parts of the immune function varied in response to interactions between carbohydrates, protein, and intake, but protein reductions had the largest impacts-mostly detrimental. In addition, our data suggest that diet quality mediates the relationship between performance (growth and survival)and immune function, as well as trade-offs among different components of immune function. Our work is the first to examine the interplay between nutrition, performance, and immune function with the geometric framework in a specialist insect herbivore.
Keywords: CARBOHYDRATES; GEOMETRIC FRAMEWORK; IMMUNE FUNCTION; PROTEIN